Metabolic control and depression in type 1 diabetes mellitus - Tatiana Vyacheslavovna Mokhort; Yana Leonidovna Navmenova (Сахарный диабет)
The most common mental disorder in patients with diabetes mellitus (DM) is depression (DS). Despite the large number of papers about DS in DM, its prevalence in type 1 DM (T1DM) remains unclear. Aim. The aim of this study was to investigate the prevalence of DS in T1DM and its possible association with metabolic control disorders. Materials and Methods. The study included 163 patients with T1DM. The patients were aged 18?65 years, and the mean duration of T1DM was 11.18 years (range 4.28?22.33 years). The control group included 75 apparently healthy individuals. The subjects underwent physical examination, and the standard self-report Hospital Anxiety and Depression Scale questionnaire was administered to evaluate the level of anxiety and DS. Psychological counselling was conducted to diagnose DS and its severity. The continuous glucose monitoring system (CGMS) was used to monitor interstitial fluid glucose levels. Statistical analysis was conducted using SPSS Statistics 17.0 and StatSoft Statistica 6.0. Results. The prevalence of DS among the patients with T1DM was much higher (approximately two-fold) than the prevalence among the healthy individuals. Female sex and age over 40 years were associated with the presence of DS. Conclusion. The development of DS in patients with T1DM is accompanied by poor glycaemic control and increased risk of hypoglycaemic episodes.